Smartphone Activation of Citizen Responders to Facilitate Defibrillation in Out-of-Hospital Cardiac Arrest - Andelius, Linn; Malta Hansen, Carolina; Lippert, Freddy K; Karlsson, Lena; Torp-Pedersen, Christian; Kjær Ersbøll, Annette; Køber, Lars; Collatz Christensen, Helle; Blomberg, Stig Nikolaj; Gislason, Gunnar H; Folke, Fredrik (Journal of the American College of Cardiology, 2020)
Dispatching citizen responders through a smartphone application (app) holds the potential to increase bystander cardiopulmonary resuscitation (CPR) and defibrillation in out-of-hospital cardiac arrest (OHCA). This study investigated arrival at the OHCA location of app-dispatched citizen responders before the Emergency Medical Services (EMS) and the association with bystander CPR and bystander defibrillation. Suspected OHCAs with alerted citizen responders from September 1, 2017, to August 31, 2018, were included. Citizen responders located 1.8 km (1.1 miles) from the OHCA were dispatched to start CPR or retrieve an automated external defibrillator. OHCAs where at least 1 citizen responder arrived before EMS were compared with OHCAs where EMS arrived first. In both groups, random bystanders could be present before the arrival of citizen responders and the EMS. Primary outcomes were bystander CPR and bystander defibrillation, which included CPR and defibrillation by citizen responders and random bystanders. Citizen responders were alerted in 819 suspected OHCAs, of which 438 (53.5%) were confirmed cardiac arrests eligible for inclusion. At least 1 citizen responder arrived before EMS in 42.0% (n = 184) of all included OHCAs. When citizen responders arrived before EMS, the odds for bystander CPR increased (odds ratio: 1.76; 95% confidence interval: 1.07 to 2.91; p = 0.027) and the odds for bystander defibrillation more than tripled (odds ratio: 3.73; 95% confidence interval: 2.04 to 6.84; p < 0.001) compared with OHCAs in which citizen responders arrived after EMS. Arrival of app-dispatched citizen responders before EMS was associated with increased odds for bystander CPR and a more than 3-fold increase in odds for bystander defibrillation. (The HeartRunner Trial; NCT03835403).